2007
DOI: 10.1063/1.2747592
|View full text |Cite
|
Sign up to set email alerts
|

Effect of surface oxidation on electron transport in InN thin films

Abstract: The chemical and electron transport properties of oxidized indium nitride epilayers and indium oxide/indium nitride heterostructures are reported. It is shown that the accumulation of electrons at the InN surface can be manipulated by the formation of a thin surface oxide layer using an ozone-assisted oxidation processing. It results in improved transport properties and in a reduction of the electron sheet concentration of the InN epilayer caused by a passivation of the surface donors and a shift of the electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
9
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 35 publications
2
9
0
Order By: Relevance
“…For instance, oxidation of the InN surface has been shown to result in a decrease in the net free-electron density. 23 In conclusion, we have shown that the variation in the bulk free electron density with film thickness does not follow the models accounting for a constant background electron density and free electrons from nitrogen vacancies along dislocations, indicating the existence of an additional thicknessdependent doping mechanism. TEM studies showing a nearly constant density of dislocations above a thickness of 250 nm provide further support.…”
mentioning
confidence: 94%
“…For instance, oxidation of the InN surface has been shown to result in a decrease in the net free-electron density. 23 In conclusion, we have shown that the variation in the bulk free electron density with film thickness does not follow the models accounting for a constant background electron density and free electrons from nitrogen vacancies along dislocations, indicating the existence of an additional thicknessdependent doping mechanism. TEM studies showing a nearly constant density of dislocations above a thickness of 250 nm provide further support.…”
mentioning
confidence: 94%
“…However, InN films usually contain a high density of dislocations due to a large lattice mismatch between the epitaxial films and substrates. Although the most commonly used substrate for the epitaxy of c ‐plane InN is GaN 5–7, the lattice‐mismatch between GaN and InN is as large as 11%. It is known that these defects are, at least, partially responsible for the difficulty in control of carrier concentration in this material 3, 4.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, two-dimensional electron gas (2DEG) is formed at the surface due to strong downwards band bending. Several studies were performed to modify concentration of 2DEG on InN surface, such as oxidation of InN surface [14,15], introduction of magnesium dopants [16], treatment of InN surface with HCl [6], and monolayer coverage of alkali metal [17]. However, all of these surface treatment procedures led to reduction of the surface electron accumulation.…”
Section: Introductionmentioning
confidence: 99%